Bodily self-awareness and object perception - Gallagher, Shaun (Theoria et Historia Scientiarum, 2007)
In this paper I would like to argue that proprioceptive awareness (including both somatic and ecological proprioception) is primarily a form of non-perceptual awareness. This might seem to be an obscure point, but it turns out to be philosophically significant in regard to what Shoemaker calls ‘immunity to error through misidentification’. Although it is possible to make a mistake in identifying one’s body via sense-perceptual modalities such as vision, some philosophers argue that one is immune to error through misidentification in regard to knowing one’s own body by means of proprioception (Cassam, 1995; Evans, 1982). If proprioception were a form of perception then it would be possible for one to proprioceptively misidentify oneself in referring to one’s body. In arguing that proprioception is not a form of perception I am defending the immunity principle in this regard.